Peranan Tata Usaha Bagian Umum Kantor Bupati Deli Serdang dalam Meningkatkan Pelayanan - Beni Cahyadi; Abdul Kadir (Universitas Medan Area, 2015)
This study aims to look at the role of public administration office part Regent of Deli Serdang in improving services to the public. Quality of service can also be viewed on the quality of services delivered. Quality of service is best called excellent service that is the best form of service exceed, surpass, surpass the services provided by the other party or of the service time ago. Office administration common parts is one of the spearheads of Deli Serdang regency government dealing directly with the public must be implemented efficiently and effective. Along with the rapid development and increasingly complex needs of people deli serdang resulted in increasingly critical public with the services provided by the government serdang deli that had not been optimal and have a number of effective and efficient. So most people expect government employees serdang deli Deli Serdang regency administration particularly common parts can provide the best service. The method used manifold qualitative descriptive approach through data collection methods that are based on a literature review and in-depth interviews. The results of this study found the presence of the weaknesses in local government personnel in achieving maximum performance.